Ekranisasi Novel Antares Karya Rweinda Ke Film Antares Karya Rizal Mantovani - Mansyah, Robbi; Wardiah, Dessy; Hetilaniar, Hetilaniar (Indonesian Research Journal on Education, 2022)
This research is titled "Ekranization of Antares novel by Rweinda to Antares movie by RizalMantovani". This research examines the process of transferring vehicles that cause various changes using the organizational approach. This research aims to describe the storyline, characters, and atmosphere in the form of aspects of shrinkage, addition, and varied changes in the mechanization of the novel to the film Antares. The data sources of this research are the novel Antares by Rweinda and the movie Antares by Rizal Mantovani. The theories used in this research are the theory of ekranization by Pemusuk Eneste and the theory of vehicle transfer by Sapardi Djoko Damono. The method used in this research is the descriptive qualitative research method. Data collection in this research uses documentation. The data analysis technique used is the content analysis technique. Overall, the shrinkage, addition, and change of variations made in the visualization of the film are still reasonable because the cuts, additions, and changes in the variation of the story are taken incertain parts that have changed. The results of the research on the novel to the Antares film for thecharacter category are shrinkage of 21, the addition of 8, and varied changes totaling 3, while the story category is shrinkage of 34, the addition of 30, varied changes of 27, the last category of the atmosphere is, shrinkage of 8, the addition of 1, and varied changes totaling 2 atmospheres.